(untitled) - Vollath, Dieter (Weinheim, 2013)
This full-colored introduction to nanomaterials and nanotechnology in particular addresses the needs of engineers who need to know the special phenomena and potentials, without getting bogged down in the scientific detail of the physics and chemistry involved.
Keywords: Nanostructured materials,Vật liệu cấu trúc nano